The Effect of Critical Thinking Ability on Independent Learning Interest of XI Social Studies Class Students of SMA Negeri 09 Kaur - Hendo Andika; Hilyati Milla; Rossa Ayuni (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the critical thinking skills of class XI IPS students at SMA Negeri 09 Kaur, to determine the interest in independent learning of students in class XI IPS SMA Negeri 09 Kaur and to determine the effect of critical thinking skills on the interest in independent learning of students in class XI IPS SMA Negeri 09 Kaur. The type of research used in this study is a type of quantitative research. The population in this study were all students of SMA Negeri 09 Kaur. The sample in this study was 30 students of class XI IPS at SMA Negeri 09 Kaur. Data collection techniques used in this study were observation, questionnaires and documentation. The data analysis technique used is simple linear regression, determining simple linear regression equations by calculating the average and testing the regression linearity using the ANOVA table. Based on the results of the analysis of research data and the discussion that has been carried out, it can be concluded that there is an influence of critical thinking skills on the interest in independent learning of class XI IPS students of SMA Negeri 09. It can be concluded that the ability to think scores reach 38.8, the number lies between 38-46 in the criteria table assessment with a very good category, this shows the ability to think critically is very good. Interest in learning scores reached 34.7 based on the assessment criteria table. This figure is between 29-37, with a fairly good category. This means that interest in independent learning is quite good. Based on the results of statistical data analysis carried out using the simple linear regression formula, the value of the simple linear regression equation is Y = 0.957 + 0.870X. Based on these results, we get Fcount of 77.88 and Ftable at a significant level of 5% of 4.20. If Fcount is greater than Ftable then Ho is rejected and Ha is accepted (77.88> 4.20), so it can be concluded that there is a positive and significant influence on critical thinking skills and interest in independent learning. Furthermore, testing the determinant coefficient r2 = 0.735 or 73.5% critical thinking ability is influenced by interest in independent learning, while the rest is influenced by other variables of 26.5%.